2015
DOI: 10.1007/s11101-015-9428-y
|View full text |Cite
|
Sign up to set email alerts
|

Artichoke: botanical, agronomical, phytochemical, and pharmacological overview

Abstract: Artichoke, Cynaracardunculus, is a dietary and medicinal plant species with a long tradition of use dating back to the ancient Egyptians, Greeks, and Romans. It comprises the globe artichoke, C. cardunculus subsp. scolymus, the cultivated cardoon, C. cardunculus subsp. altilis, and the wild cardoon, C. cardunculus subsp. sylvestris. The edible part of the plant is limited to the fleshy leaves (bracts) and receptacle of a large immature inflorescence, named capitulum or head, that has been shown to be a rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(154 citation statements)
references
References 81 publications
(110 reference statements)
7
143
0
4
Order By: Relevance
“…However, these studies were carried out mainly in European Countries (Pagano et al, 2016;Petrovic et al, 2008;Falco et al, 2015;Kaymaz et al, 2017). In this study, the absence of cynarin was noted in the leaf extract and two of the three commercial herbal medicines.…”
Section: Evaluation Of Commercial Products and Dry Leaf Extractmentioning
confidence: 99%
“…However, these studies were carried out mainly in European Countries (Pagano et al, 2016;Petrovic et al, 2008;Falco et al, 2015;Kaymaz et al, 2017). In this study, the absence of cynarin was noted in the leaf extract and two of the three commercial herbal medicines.…”
Section: Evaluation Of Commercial Products and Dry Leaf Extractmentioning
confidence: 99%
“…30%, and a number of subtypes (a, b, and so on) with ∼20% sequence divergence. [11][12][13][14] According to FAO, Egypt is the second top country, after Italy, for producing artichoke in 2010 and 2011, † and is a major vegetable component of the Mediterranean diet. 6,7 HCV is currently the major burden on the health care system in Egypt with infection prevalence almost 10 times greater than any other country in the world and the highest prevalence of HCV genotype 4.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 HCV is currently the major burden on the health care system in Egypt with infection prevalence almost 10 times greater than any other country in the world and the highest prevalence of HCV genotype 4. [12][13][14]16,17 Additionally, the efficacy and tolerability of coated tablets containing 450 mg artichoke dry extract (CY450, Valverde ® ) were clinically investigated in the treatment of hyperlipoproteinemia and compared with placebo revealed that artichoke is an effective agent for reducing cholesterol. 9 Several plants are used for the treatment of liver problems and HCV infections including milk thistle seed, artichoke, licorice, turmeric, ginseng, carob, nettle seed, nigella, ginger and taraxacum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations